DEVELOPING EFFICIENT WEBQUEST–BASED INSTRUCTION THROUGH ONLINE SOCIAL NETWORK FOR ENHANCING ANALYTICAL THINKING SKILL, EVALUATIVE THINKING, AND SELF-DIRECTED LEARNING BEHAVIOR OF TEACHER EDUCATION STUDENTS: การพัฒนาบทเรียนแสวงรู้บนเว็บผ่านสื่อสังคมออนไลน์ที่มีประสิทธิภาพ เพื่อสร้างเสริมทักษะการคิดวิเคราะห์ การคิดเชิงประเมิน และพฤติกรรมการเรียนรู้แบบนำตนเองของนักศึกษาครู - Isarapreeda, Waranan (Journal of Education and Innovation, 2019)
The purposes of this study were to 1) develop the WebQuest–based instruction through online social network with a required efficiency according to Meguigans criterion, 2) to compare learning achievement, analytical thinking skill, evaluative thinking, and self-directed learning behavior of WebQuest instruction group students between pretest and posttest, 3) to compare learning achievement, analytical thinking skill, evaluative thinking, and self-directed learning behavior between WebQuest instruction group and traditional instruction group, and 4) to investigate students’ satisfaction toward WebQuest instruction. Samples consisted of two groups of bachelor in education program students, Bansomdejchaopraya Rajabhat University who registered for the course of data communication and computer network in school, obtained by random assignment into WebQuest instructional group and traditional instructional group, 30 of each. Both groups were assessed a pretest and posttest and studied in the same topics for 8 weeks. Instruments used in the study were WebQuest–based instruction through online social network, learning achievement test, analytical thinking skill test, questionnaires of evaluative thinking, self-directed learning behavior, and satisfaction toward the WebQuest instruction. The data were then analyzed using Mean, Standard Deviation, and t-test. The findings revealed that 1) the WebQuest–based instruction through online social network showed an efficiency ratio of 1.12, met the Meguigans criterion, 2) posttest mean scores of learning achievement, analytical thinking skill, evaluative thinking, and self-directed learning behavior of WebQuest instruction group were statistically significant higher than pretest mean scores, and 3) posttest mean scores of learning achievement, analytical thinking skill, evaluative thinking, and self-directed learning behavior of the WebQuest instruction group were statistically significant higher than the traditional instruction group, and 4) the overall satisfaction of students learning through the WebQuest lesson was found at a high level.